2015
DOI: 10.1007/s11011-015-9731-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and metabolic markers and short-time outcome in patients with acute ischemic stroke in relation to TOAST subtypes

Abstract: The aim of this study was to evaluate the association between inflammatory and metabolic markers and short-time outcome with acute ischemic stroke subtypes. A total of 121 patients was classified according to TOAST criteria, such as large artery atherosclerosis (LAAS), lacunar infarct (LAC), cardioembolic infarct (CEI), other determined etiology (ODE), and undetermined etiology (UDE). The functional impairment was evaluated within the first eight hours of stroke and the outcome after three-month follow-up usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 94 publications
0
17
1
Order By: Relevance
“…This can be another evidence that links BBB disruption and CE. Moreover, previous studies revealed that C-reactive protein (CRP) was higher in patients with CE ( 28 , 29 ). It has been proved that CRP could cause endothelial cells contraction, which went along with disruption of tight junction molecules and finally resulting in BBB disruption ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be another evidence that links BBB disruption and CE. Moreover, previous studies revealed that C-reactive protein (CRP) was higher in patients with CE ( 28 , 29 ). It has been proved that CRP could cause endothelial cells contraction, which went along with disruption of tight junction molecules and finally resulting in BBB disruption ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the rapid diagnosis of AIS and the prediction of neurological deficit or mortality. Some of the markers whose value in diagnosis and predicting mortality and prognosis that have recently been investigated are glucose, iron, ferritin, homocysteine, insulin, P-selectin, matrix metalloproteinase-9, high-density lipoprotein cholesterol, platelets, C-reactive protein, glial fibrillary acidic protein, TNF-α, interleukin-6, and proenkephalin-A ( 14 , 15 , 16 , 17 , 18 , 19 ). Recently, sTWEAK has become a highly investigated protein, mainly due to its effect on apoptosis stimulation and inflammatory cytokine release ( 6 , 7 , 8 , 9 , 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The highest concentration of IL-6 in plasma and other immune-inflammatory and thromboembolic/fibrinolytic agents (PAI-1, TPA) was found in patients with cardiogenic stroke caused by a cardiac embolism. 48,67 This group of patients was observed with not only an increased immune-inflammatory activity but also with a greater degree of neurological deficit as assessed according to the Scandinavian Stroke Scale (SSS). 48 In a lacunar stroke, which is caused by cerebral microangiopathy, lower levels of pro-inflammatory cytokines (IL-6 and TNF-α) in plasma and lower P-selectin and ICAM-1 (intercellular adhesion molecule-1) were observed.…”
Section: Interleukinsmentioning
confidence: 99%